2019
DOI: 10.1002/jcb.28742
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of potential drugs and targets based on meibomian gland dysfunction module classification to guide individualized treatment

Abstract: Meibomian gland dysfunction (MGD) is an epidemic chronic ocular inflammation. However, little is known about its effective treatment. Here, this study identified important MGD‐related genes, core regulators, and potential drugs and their targets though integrating a series of bioinformational analyses. First, there were 665 differentially expression genes (DEGs) were identified. Then, 56 coexpression modules were exacted based on the expression of DEGs and their interactors. Moreover, core transcription factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…The most highly upregulated protein was mucin-like protein 1. This protein is associated with meibomian gland (MG) dysfunction [ 50 ]. MGs are found in the upper and lower lids of the eyes, and it is not unlikely that these glands were affected by the RT in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The most highly upregulated protein was mucin-like protein 1. This protein is associated with meibomian gland (MG) dysfunction [ 50 ]. MGs are found in the upper and lower lids of the eyes, and it is not unlikely that these glands were affected by the RT in our study.…”
Section: Discussionmentioning
confidence: 99%
“…They are reported to be more common in the upper lid where there is a higher density of Meibomian glands [23,63]. The histomorphologic features of sebaceous glands from tamoxifen-inducible cMYC mice are well documented, and a few studies have identified MYC as a differentially expressed transcription factor and potential therapeutic target in Meibomian gland dysfunction [64][65][66][67][68][69][70]. However, few studies interrogating MYC expression in normal Meibomian glands have been published.…”
Section: Discussionmentioning
confidence: 99%